2006
DOI: 10.1093/sleep/29.12.1643
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Treatment Seeking in Primary Insomnia in the United Kingdom: A Cross-Sectional Perspective

Abstract: Given the chronicity and serious adverse consequences of insomnia, this study suggests that programs of public health awareness designed to reduce the perception of insomnia as trivial and to increase awareness of the effective treatments available may be important for reducing the prevalence of insomnia in the United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 0 publications
3
59
1
2
Order By: Relevance
“…Although low rates of insomnia recognition can be a result of the inherent resistance among insomnia patients to seek professional help (Aikens and Rouse 2005;Stinson et al 2006;Angst et al 2010), the suboptimal management of insomnia might reflect a more complex problem in primary care practice. Drawing on exploratory studies there appears to be a gap between clinical definitions of insomnia and patient definitions of insomnia.…”
Section: Managing Insomnia In Primary Carementioning
confidence: 99%
“…Although low rates of insomnia recognition can be a result of the inherent resistance among insomnia patients to seek professional help (Aikens and Rouse 2005;Stinson et al 2006;Angst et al 2010), the suboptimal management of insomnia might reflect a more complex problem in primary care practice. Drawing on exploratory studies there appears to be a gap between clinical definitions of insomnia and patient definitions of insomnia.…”
Section: Managing Insomnia In Primary Carementioning
confidence: 99%
“…In a telephone survey of the general population conducted in Canada, Morin and colleagues (2006b) found that only 42.3% of those people with diagnosable insomnia had consulted their GP regarding their sleeping difficulties. Additional barriers to seeking help might include a tendency to minimise problems, and a lack of awareness of treatment options available Stinson, Tang & Harvey, 2006). …”
Section: Access To Treatment For Insomniamentioning
confidence: 99%
“…Research has shown that sleep education may function as a first-line intervention in a stepped-care model for individuals who want to improve their sleep, but are unlikely to reach threshold for, or seek, more substantial clinical treatment (Irish, Kline, Gunn, Buysse, & Hall, 2015;Morin, LeBlanc, et al, 2006;Stinson et al, 2006). In the last few years, CBT has become an important treatment option within mental health care services, including the Improving Access to Psychological Therapies (IAPT) initiative in the UK.…”
Section: Practical Information and Techniquesmentioning
confidence: 99%